Bisnis Ikan Gabus Dalam Bidang Kewirausahaan Perikanan - Zega, Hude Venial (CV. SINAR HOWUHOWU, 2025)
The snakehead fish business is one of the promising business opportunities in the field of fisheries entrepreneurship. Snakehead fish (Channa striata) is a freshwater fish commodity with high economic value and nutritional content, particularly protein and albumin, which are beneficial for human health. This study aims to analyze the potential of the snakehead fish business from the perspective of fisheries entrepreneurship, covering production aspects, business management, marketing strategies, as well as challenges and development opportunities. The research employed a descriptive qualitative approach supported by simple quantitative data. Data were collected through observation, interviews, and documentation involving snakehead fish business operators. The results indicate that the snakehead fish business has considerable profit potential due to its relatively simple and flexible cultivation system. Product diversification through processing of snakehead fish products was proven to increase added value and business competitiveness. However, several constraints remain, including limited capital, fluctuating feed prices, and insufficient knowledge of business management and marketing. Therefore, innovative development strategies, capacity building for entrepreneurs, and support from relevant stakeholders are necessary to ensure the sustainable development of the snakehead fish business and its contribution to community welfare and the strengthening of the fisheries sector.